THE QUR’ANIC JESUS - Waryono Abdul Ghafur; Zaenuddin Hudi Prasojo; Mohammed Sahrin Bin Haji Masri (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2019)
This article examines the theological polemics between Islam and Christianity focusing on the prophetic attribution of Isa al-Masih in Islamic tradition. It takes a close look at the Qur’anic construction upon the Prophet Isa al-Masih as a human being who served as a messenger of God, while briefly comparing the Islamic construction to the Christian tradition projecting Isa-al-Masih as the son of God. Rather than emphasising differences between the two traditions, this article, through the Quranic concept kalimatun sawa’ (the shared principle or meeting point), sheds a new light on a shared belief between Islam and Christian traditions. Both Islam and Christianity believe that Isa al-Masih is the saviour for humanity, the liberator for the weak and the oppressed. The Qur’an maintains Isa al-Masih as one of the ulul azmi meaning that the prophets who successfully liberated his people.